Blockade of the mineralocorticoid receptors in the medial prefrontal cortex prevents the acquisition of one-trial tolerance in mice - Albernaz-Mariano, Kairo Alan [UNESP] (2022)
One-trial tolerance (OTT) is characterized by the lack of anxiolytic-like effects of benzodiazepines in animals submitted to a trial 2 in the elevated plus-maze (EPM) and is described to be influenced by learning mechanisms. Mineralocorticoid receptors (MR) in the infralimbic subregion (IL) of the medial prefrontal cortex (mPFC) are important modulators of emotional learning, but the MR involvement in the establishment of OTT remains unclear. We investigated the effects of intra-IL infusions of RU 28318 (an MR antagonist) on the OTT to the anxiolytic effects of midazolam (MDZ, GABAA-benzodiazepine agonist) in mice exposed to a two-trial protocol in the EPM. First, mice were treated with saline or MDZ (2 mg/kg, i.p.) 30 min before trial 1 or 2 in the EPM, to characterize the OTT. To investigate the role of MR in the OTT, independent groups of mice received intra-IL infusions of vehicle or RU 28318 (5 or 10 ng/0.1 µL) immediately before or after first trial in the EPM. Twenty-four hours later, the same mice received injections of saline or MDZ and were re-tested in the EPM. The MDZ decreased anxiety-like behaviors in trial 1, but the same anxiolytic-like effect was not observed in MDZ-mice prior to the second EPM test, confirming the OTT. Blockade of MR in the IL before, but not after, trial 1 restored the anxiolytic effects if MDZ administered in trial 2. These findings indicate that the MR in the IL-mPFC contributing to the OTT by mediating the acquisition, but not the consolidation of emotional learning.